A Method for Attitude Control Based on a Mathematical Model for an Inverted Pendulum-Type Mobile Robot - Jin-Ho Yoon; Myung-Jin Chung (Institute of Advanced Engineering and Science, 2016)
A method for attitude control based on a mathematical model for an inverted pendulum-type mobile robot was proposed. The inverted pendulum-type mobile robot was designed and the mathematical modeling was conducted. The parameters of the mobile robot were estimated and the state-space model of mobile robot was obtained by the substitution of the estimated parameters into the mathematical model. The transfer function of the mobile robot is applied to generate the root-locus diagram used for the estimation of the gains of the PID controller. The attitude control method including a PID controller, non-linear elements, and integral saturation prevention was designed and simulated. The experiment was conducted by applying the method to the mobile robot. In the attitude control experiment, the performance of attitude recovery from ±12° tilted initial state with a settling time of 0.98s and a percent overshoot of 40.1% was obtained. Furthermore, the attitude maintaining robustness against disturbance was verified.